Les Vingt Amériques latines : . Édition entièrement revue et augmentée - Niedergang, Marcel (1922-2001)
Politique. 26-28 1. Brésil, Argentine, Uruguay, Paraguay ; 2. Chili, Bolivie, Pérou, Équateur, Colombie, Vénézuéla ; 3. Mexique, Guatemala, Honduras, San-Salvador, Nicaragua, Costa Rica, Panama, Haïti, Saint-Domingue, Cuba